Impact of Population-Based Screening for Diabetes and Prediabetes Among 67-Year-Olds Using Point-of-Care HbA1c on Healthcare Ultilisation, Results from the VISP Cohort - Andersen JW; Høgh A; Lindholt JS; Søgaard R; Støvring H; Yderstræde KB; Sandbæk A; Dahl M (Clinical Epidemiology)
Jesper Winkler Andersen,1,2 Annette Høgh,1,3 Jes Sanddal Lindholt,1,3– 6 Rikke Søgaard,5 Henrik Støvring,3,7 Knud Bonnet Yderstræde,5,8 Annelli Sandbæk,9– 11 Marie Dahl1,3– 5 1Vascular Research Unit, Department of Vascular Surgery, Viborg Regional Hospital, Viborg, Denmark; 2Department of Gastroenterology, Aarhus University Hospital, Aarhus, Denmark; 3Department of Clinical Medicine, Aarhus University, Aarhus, Denmark; 4Department of Cardiothoracic and Vascular Surgery, Odense University Hospital, Odense, Denmark; 5Department of Clinical Research, University of Southern Denmark, Odense, Denmark; 6Elite Centre of Individualized Treatment of Arterial Diseases (CIMA), Odense University Hospital, Odense, Denmark; 7Department of Biomedicine, Aarhus University, Aarhus, Denmark; 8Diabetes Center, Steno, Odense, Denmark; 9Department of Public Health, Aarhus University, Aarhus, Denmark; 10Research unit of General Medical Practice, Aarhus University, Aarhus, Denmark; 11Steno Diabetes Center Aarhus, Aarhus University Hospital, Aarhus, DenmarkCorrespondence: Jesper Winkler Andersen, Vascular Research Unit, Department of Surgery, Viborg Regional Hospital, Toldbodgade 12, Viborg, 8800, Denmark, Tel +45 28118736, Email jesper.andersen@midt.rm.dkPurpose: The present study aims to evaluate the changes in healthcare utilization following population-based screening for diabetes mellitus (DM) using point-of-care HbA1c measurement in the Viborg Screening Program (VISP) cohort, which invites all 67-year-olds in Viborg, Denmark, for cardiovascular disease (CVD) and DM screening.Patients and Methods: We conducted a cohort study using data from VISP and Danish national health registers. The study included 2386 individuals invited to VISP from August 1, 2014, to May 31, 2017. Exclusion criteria were non-attenders, those with prior DM, and those with missing HbA1c measurements. Pre- and post-screening healthcare utilization was analyzed, stratified by HbA1c levels: < 42 mmol/mol (normal), 42– 48 mmol/mol (pre-DM), and ≥ 48 mmol/mol (DM). Statistical analyses were performed using Poisson and logistic regression models to compare ratios of healthcare utilization before and after screening.Results: Of the participants, 16.5% had pre-DM, and 3.4% had DM. Screening resulted in increased general physician contacts across all HbA1c groups, the highest increase was seen in the DM group with a pre- vs post-screening odds ratio [OR] of 3.25 (95% CI: 1.06– 9.95) and a relative odds ratio [ROR] of 2.70 (0.87– 8.39). Also, in this group, the OR for having ≥ 1 HbA1c measurement one year pre- vs post-screening was 5.56 (2.77 − 11.14) and 26.8% (17.6– 37.9) started glucose-lowering treatment within two years post-screening. Despite expectations, healthcare utilization did not decrease among those with normal HbA1c levels.Conclusion: Population-based screening for DM and CVD among 67-year-olds resulted in increased healthcare utilization, particularly among those with screen-detected DM and pre-DM. The anticipated reduction in healthcare utilization among individuals with normal HbA1c levels was not observed. These findings highlight the potential for screening to enhance disease management and underscore the need for strategies to optimize healthcare resource use following screening, especially for individuals without DM.Trial Registration: NCT03395509.Keywords: epidemiology, medication, general practice, Denmark, diabetes